2021
DOI: 10.1155/2021/9862066
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression Profiles and Functional Prediction of circRNAs in Necrotizing Enterocolitis

Abstract: Circular RNAs (circRNAs), a novel type of noncoding RNAs, have been demonstrated to behave as microRNA (miRNA) sponges to exert their effects during pathological processes of diseases. However, the roles of circRNAs have not been explored in necrotizing enterocolitis (NEC). This study sought to identify differentially expressed circRNAs and predict their potential biological functions in NEC. circRNA expression profiles in terminal ileum from newborn rats with NEC and normal controls were explored using next-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Changes in gene expression of the whole blood are mainly related to severe NEC, and their expression in mild NEC changes slightly (48). Compared to normal controls, 53 circular RNAs have been found to change in the NEC group (49). In recent years, studies have identified some DEGs in infants with NEC.…”
Section: Erentially Expressed Genesmentioning
confidence: 99%
“…Changes in gene expression of the whole blood are mainly related to severe NEC, and their expression in mild NEC changes slightly (48). Compared to normal controls, 53 circular RNAs have been found to change in the NEC group (49). In recent years, studies have identified some DEGs in infants with NEC.…”
Section: Erentially Expressed Genesmentioning
confidence: 99%
“…It is well recognized that nucleic-acid and RNA sensing pathways are relevant beyond microbial sensing, and have been documented to contribute to various inflammatory disease models (113). Non-coding RNAs have been previously implicated in gastrointestinal disease pathology, including IBD and colitis (48). miRNAs have been implicated to impact biological functions in gastrointestinal diseases, such as through affecting cell apoptosis, cell proliferation, intestinal epithelial barrier function, and inflammation infiltration by post-transcriptional gene silencing (114).…”
Section: Non-coding Rnamentioning
confidence: 99%
“…Intestinal epithelial cell death and breach of mucosal integrity is an important initiating process in NEC development. Certain RNAs have been implicated in this process, for example, circular RNAs (circRNA) were differentially expressed in an animal NEC model and impacted apoptotic signaling and death receptor activity, thereby contributing to cell death (48). Many differentially expressed miRNAs have been identified in NEC impacting intestinal epithelial cell death, including, miR-200a-3p, miR-141-3p, miR-431, and miR-21 (40,42,51,53,59).…”
Section: Non-coding Rnamentioning
confidence: 99%